2019
DOI: 10.1001/jamanetworkopen.2019.12666
|View full text |Cite
|
Sign up to set email alerts
|

Association of Treatments for Myeloproliferative Neoplasms During Pregnancy With Birth Rates and Maternal Outcomes

Abstract: Key PointsQuestionAre use of aspirin, heparin, interferon, or combinations associated with live birth rate and adverse maternal outcomes in pregnant women with myeloproliferative neoplasms?FindingsIn this systematic review and meta-analysis of 22 studies, reporting on 1210 pregnancies, the live birth rate was 71.3%; most studies reported on pregnancy with essential thrombocythemia. The use of aspirin and interferon—but not heparin—was associated with higher odds of live birth.MeaningModerate-quality evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 64 publications
(167 reference statements)
4
51
0
Order By: Relevance
“…NSAIDs, [38][39][40][41][42][43][44][45] two antiepileptics, [46][47][48] two β-blockers, [49][50][51] two calcium channel blockers, 50,52 two antiemetics (5-HT3 receptor antagonists), 53,54 two antipsychotics, 55,56 two antihistamines, 57,58 and one each assessed serotonin and norepinephrine reuptake inhibitors (SNRIs), 59,60 tricyclic antidepressants, 59,60 benzodiazepines, 61,62 corticosteroids, 63 oral magnesium, 64 triptans (5-HT1B/1D receptor agonists), 65 analgesics/antipyretics, 66 and intravenous magnesium. 67 Twelve SRs reported maternal adverse effects and 23 reported fetal/child adverse effects.…”
Section: All 26 Srs Assessed Pharmacologic Interventions: Eight Assessedmentioning
confidence: 99%
“…NSAIDs, [38][39][40][41][42][43][44][45] two antiepileptics, [46][47][48] two β-blockers, [49][50][51] two calcium channel blockers, 50,52 two antiemetics (5-HT3 receptor antagonists), 53,54 two antipsychotics, 55,56 two antihistamines, 57,58 and one each assessed serotonin and norepinephrine reuptake inhibitors (SNRIs), 59,60 tricyclic antidepressants, 59,60 benzodiazepines, 61,62 corticosteroids, 63 oral magnesium, 64 triptans (5-HT1B/1D receptor agonists), 65 analgesics/antipyretics, 66 and intravenous magnesium. 67 Twelve SRs reported maternal adverse effects and 23 reported fetal/child adverse effects.…”
Section: All 26 Srs Assessed Pharmacologic Interventions: Eight Assessedmentioning
confidence: 99%
“…However, MPN patients are at increased risk for pregnancy related complications, the most common being spontaneous abortion. Other common pregnancy related complications include higher risk for thrombosis and hemorrhage, pre-eclampsia, and stillbirths [70,72,73]. Cytoreduction is considered in patients who have higher risk features following guidelines for cytoreduction in MPN and may be given in those with prior pregnancy losses and/or complications, history of thrombosis, or extreme thrombocytosis leading to increased risk of bleeding [33,70,74].…”
Section: Pregnant Populationsmentioning
confidence: 99%
“…Of 78 pregnancies treated with interferon reported in the literature, the live birth rate was 94%, with no fetal malformations [70]. Indeed, a meta-analysis showed improved live birth rates in ET women who were treated with interferon during their pregnancy [73]. Despite the association with improved outcomes, interferon use is typically reserved for high-risk pregnancies and it is unknown whether there would be any benefit in patients without traditional indication for cytoreduction.…”
Section: Pregnant Populationsmentioning
confidence: 99%
“…A recent meta-analysis reported that the live birth rate was higher in pregnant women with MPNs who received low-dose aspirin during pregnancy than in those managed with observation alone (odds ratio, 9.48; 95% confidence interval, 4.41 to 20.41) [ 74 ]. Low-molecular-weight heparin may reduce the risk of venous thromboembolism in the antepartum and postpartum periods without increasing the risk of bleeding, although the venous thromboembolism risk was not significantly different between pregnant patients with ET who used low-molecular-weight heparin and those who did not [ 75 ].…”
Section: Pregnant Women and Those Who Desire To Become Pregnantmentioning
confidence: 99%
“…Currently, both hydroxyurea and anagrelide are contraindicated for use during pregnancy. The only drug with proven safety and cytoreduction effects in pregnant patients is standard IFN-α[70][71][72][73].A recent meta-analysis reported that the live birth rate was higher in pregnant women with MPN who received low-dose aspirin during pregnancy than in those managed with observation alone (OR, 9.48; 95% CI, 4.41 -20.41)[74]. Low molecular weight heparin (LMWH) may reduce the risk of venous thromboembolism in the antepartum and postpartum periods without increasing the risk of bleeding, although the venous thromboembolism (VTE) risk was not statistically different between pregnant ET patients who did and did not use LMWH[75].…”
mentioning
confidence: 99%